Determinants of the innovative development of transport enterprises in Ukraine - Kersys, Robertas; Pererva, P. G. (Кременчуцький національний університет імені Михайла Остроградського, 2025)
The report examines the key determinants of innovative development of transport enterprises in Ukraine. Economic, technological, organizational, legal, and human capital factors shaping the industry’s ability to implement modern solutions are identified. The influence of investment attractiveness, digitalization of transport processes, infrastructure modernization, and integration of environmentally friendly technologies is analyzed. Particular attention is paid to the role of state policy, cooperation with research institutions, and the development of human capital. The necessity of a comprehensive approach to forming an innovation strategy for transport enterprises is substantiated, aimed at strengthening competitiveness and ensuring integration into the European transport space.
Keywords: innovative development; transport enterprises; determinants; digitalization; investments; innovation strategy; human capital